Synaptic organization of lobula plate tangential cells in Drosophila: Dα7 cholinergic receptors - Raghu, Shamprasad V; Maximilian Jösch; Sigrist, Stephan J; Borst, Alexander; Reiff, Dierk F (Journal of Neurogenetics)
The nervous system of seeing animals derives information about optic flow in two subsequent steps. First, local motion vectors are calculated from moving retinal images, and second, the spatial distribution of these vectors is analyzed on the dendrites of large downstream neurons. In dipteran flies, this second step relies on a set of motion-sensitive lobula plate tangential cells (LPTCs), which have been studied in great detail in large fly species. Yet, studies on neurons that convey information to LPTCs and neuroanatomical investigations that enable a mechanistic understanding of the underlying dendritic computations in LPTCs are rare. We investigated the subcellular distribution of nicotinic acetylcholine receptors (nAChRs) on two sets of LPTCs: vertical system (VS) and horizontal system (HS) cells in Drosophila melanogaster. In this paper, we describe that both cell types express Dα7-type nAChR subunits specifically on higher order dendritic branches, similar to the expression of gamma aminobutyric acid (GABA) receptors. These findings support a model in which directional selectivity of LPTCs is achieved by the dendritic integration of excitatory, cholinergic, and inhibitory GABA-ergic input from local motion detectors with opposite preferred direction. Nonetheless, whole-cell recordings in mutant flies without Dα7 nAChRs revealed that direction selectivity of VS and HS cells is largely retained. In addition, mutant LPTCs were responsive to acetylcholine and remaining nAChR receptors were labeled by α-bungarotoxin. These results in LPTCs with genetically manipulated excitatory input synapses suggest a robust cellular implementation of dendritic processing that warrants direction selectivity. The underlying mechanism that ensures appropriate nAChR-mediated synaptic currents and the functional implications of separate sets or heteromultimeric nAChRs can now be addressed in this system.

Biomimetic membrane systems to study cellular organization - Martin Loose; Schwille, Petra (Journal of Structural Biology)
During many cellular processes such as cell division, polarization and motility, the plasma membrane does not only represent a passive physical barrier, but also provides a highly dynamic platform for the interplay between lipids, membrane binding proteins and cytoskeletal elements. Even though many regulators of these interactions are known, their mutual interdependence appears to be highly complex and difficult to study in a living cell. Over the past few years, in vitro studies on membrane-cytoskeleton interactions using biomimetic membranes turned out to be extremely helpful to get better mechanistic insight into the dynamics of these processes. In this review, we discuss some of the recent developments using in vitro assays to dissect the role of the players involved: lipids in the membrane, proteins binding to membranes and proteins binding to membrane proteins. We also summarize advantages and disadvantages of supported lipid bilayers as model membrane.

Chromatin shapes the mitotic spindle - Dinarina, Ana; Pugieux, Céline; Corral, Maria M; Martin Loose; Spatz, Joachim P; Karsenti, Éric; Nédélec, François J (Cell)
In animal and plant cells, mitotic chromatin locally generates microtubules that self-organize into a mitotic spindle, and its dimensions and bipolar symmetry are essential for accurate chromosome segregation. By immobilizing microscopic chromatin-coated beads on slide surfaces using a microprinting technique, we have examined the effect of chromatin on the dimensions and symmetry of spindles in Xenopus laevis cytoplasmic extracts. While circular spots with diameters around 14-18 μm trigger bipolar spindle formation, larger spots generate an incorrect number of poles. We also examined lines of chromatin with various dimensions. Their length determined the number of poles that formed, with a 6 × 18 μm rectangular patch generating normal spindle morphology. Around longer lines, multiple poles formed and the structures were disorganized. While lines thinner than 10 μm generated symmetric structures, thicker lines induced the formation of asymmetric structures where all microtubules are on the same side of the line. Our results show that chromatin defines spindle shape and orientation. For a video summary of this article, see the PaperFlick file available with the online Supplemental Data.

Recombination rates may affect the ratio of X to autosomal noncoding polymorphism in African populations of Drosophila melanogaster - Beatriz Vicoso; Charlesworth, Brian (Genetics)

The deficit of male-biased genes on the D. melanogaster X chromosome is expression-dependent: A consequence of dosage compensation? - Beatriz Vicoso; Charlesworth, Brian (Journal of Molecular Evolution)
In Drosophila, there is a consistent deficit of male-biased genes on the X chromosome. It has been suggested that male-biased genes may evolve from initially unbiased genes as a result of increased expression levels in males. If transcription rates are limited, a large increase in expression in the testis may be harder to achieve for single-copy X-linked genes than for autosomal genes, because they are already hypertranscribed due to dosage compensation. This hypothesis predicts that the larger the increase in expression required to make a male-biased gene, the lower the chance of this being achievable if it is located on the X chromosome. Consequently, highly expressed male-biased genes should be located on the X chromosome less often than lowly expressed male-biased genes. This pattern is observed in our analysis of publicly available data, where microarray data or EST data are used to detect male-biased genes in D. melanogaster and to measure their expression levels. This is consistent with the idea that limitations in transcription rates may prevent male-biased genes from accumulating on the X chromosome.

Effective population size and the faster-X effect: An extended model - Beatriz Vicoso; Charlesworth, Brian (Evolution)
Current models of X-linked and autosomal evolutionary rates often assume that the effective population size of the X chromosome (NeX) is equal to three-quarters of the autosomal population size (NeA). However, polymorphism studies of Drosophila melanogaster and D. simulans suggest that there are often significant deviations from this value. We have computed fixation rates of beneficial and deleterious mutations at X-linked and autosomal sites when this occurs. We find that NeX/NeA is a crucial parameter for the rates of evolution of X-linked sites compared to autosomal sites. Faster-X evolution due to the fixation of beneficial mutations can occur under a much wider range of levels of dominance when NeX/N eA > 3/4. We also examined various parameters that are known to influence the rates of evolution at X-linked and autosomal sites, such as different mutation rates in males and females and mutations that are sexually antagonistic, to determine which cases can lead to faster-X evolution. We show that, when the rate of nonsynonymous evolution is normalized by the rate of neutral evolution, a sex difference in mutation rate has no influence on the conditions for faster-X evolution.

Progress and prospects toward our understanding of the evolution of dosage compensation - Beatriz Vicoso; Bachtrog, Doris (Chromosome Research)
In many eukaryotic organisms, gender is determined by a pair of heteromorphic sex chromosomes. Degeneration of the non-recombining Y chromosome is a general facet of sex chromosome evolution. Selective pressure to restore expression levels of X-linked genes relative to autosomes accompanies Y-chromosome degeneration, thus driving the evolution of dosage compensation mechanisms. This review focuses on evolutionary aspects of dosage compensation, in light of recent advances in comparative and functional genomics that have substantially increased our understanding of the molecular mechanisms of dosage compensation and how it evolved. We review processes involved in sex chromosome evolution, and discuss the dynamic interaction between Y degeneration and the acquisition of dosage compensation. We compare mechanisms of dosage compensation and the origin of dosage compensation genes between different taxa and comment on sex chromosomes that apparently lack compensation mechanisms. Finally, we discuss how dosage compensation systems can also influence the evolution of well-established sex chromosomes.

Structural basis for the mechanism of respiratory complex I - Berrisford, John M; Leonid Sazanov (Journal of Biological Chemistry)
Complex I plays a central role in cellular energy production, coupling electron transfer between NADH and quinone to proton translocation. The mechanism of this highly efficient enzyme is currently unknown. Mitochondrial complex I is a major source of reactive oxygen species, which may be one of the causes of aging. Dysfunction of complex I is implicated in many human neurodegenerative diseases. We have determined several x-ray structures of the oxidized and reduced hydrophilic domain of complex I from Thermus thermophilus at up to 3.1 Å resolution. The structures reveal the mode of interaction of complex I with NADH, explaining known kinetic data and providing implications for the mechanism of reactive oxygen species production at the flavin site of complex I. Bound metals were identified in the channel at the interface with the frataxin-like subunit Nqo15, indicating possible iron-binding sites. Conformational changes upon reduction of the complex involve adjustments in the nucleotide-binding pocket, as well as small but significant shifts of several α-helices at the interface with the membrane domain. These shifts are likely to be driven by the reduction of nearby iron-sulfur clusters N2 and N6a/b. Cluster N2 is the electron donor to quinone and is coordinated by unique motif involving two consecutive (tandem) cysteines. An unprecedented "on/off switch" (disconnection) of coordinating bonds between the tandem cysteines and this cluster was observed upon reduction. Comparison of the structures suggests a novel mechanism of coupling between electron transfer and proton translocation, combining conformational changes and protonation/deprotonation of tandem cysteines.

Reconnection in three dimensions: The role of spines in three eruptive flares - Des Jardins, Angela; Canfield, Richard; Longcope, Dana; Fordyce, Crystal; Waitukaitis, Scott R (The Astrophysical Journal)
In order to better understand magnetic reconnection and particle acceleration in solar flares, we compare the RHESSI hard X-ray (HXR) footpoint motions of three flares with a detailed study of the corresponding topology given by a Magnetic Charge Topology model. We analyze the relationship between the footpoint motions and topological spine lines and find that the examined footpoint sources move along spine lines. We present a three-dimensional topological model in which this movement can be understood. As reconnection proceeds, flux is transferred between the reconnecting domains, causing the separator to move. The movement of the separator\'s chromospheric ends, identified with the HXR footpoints, is along those spine lines on which the separator ends.

High-speed tracking of rupture and clustering in freely falling granular streams - Royer, John; Evans, Daniel; Oyarte, Loreto; Guo, Qiti; Kapit, Eliot; Möbius, Matthias; Waitukaitis, Scott R; Jaeger, Heinrich (Nature)
Thin streams of liquid commonly break up into characteristic droplet patterns owing to the surface-tension-driven PlateauRayleigh instability 1-3. Very similar patterns are observed when initially uniform streams of dry granular material break up into clusters of grains4-6, even though flows of macroscopic particles are considered to lack surface tension7,8. Recent studies on freely falling granular streams tracked fluctuations in the stream profile9, but the clustering mechanism remained unresolved because the full evolution of the instability could not be observed. Here we demonstrate that the cluster formation is driven by minute, nanoNewton cohesive forces that arise from a combination of van der Waals interactions and capillary bridges between nanometre-scale surface asperities. Our experiments involve high-speed video imaging of the granular stream in the co-moving frame, control over the properties of the grain surfaces and the use of atomic force microscopy to measure grain-grain interactions. The cohesive forces that we measure correspond to an equivalent surface tension five orders of magnitude below that, of ordinary liquids. We find that, the shapes of these weakly cohesive, non-thermal clusters of macroscopic particles closely resemble droplets resulting from thermally induced rupture of liquid nanojets 10-12.

Border control at the nucleus: Biogenesis and organization of the nuclear membrane and pore complexes - HETZER, Martin W; Wente, Susan R. (Developmental Cell)
Over the last decade, the nuclear envelope (NE) has emerged as a key component in the organization and function of the nuclear genome. As many as 100 different proteins are thought to specifically localize to this double membrane that separates the cytoplasm and the nucleoplasm of eukaryotic cells. Selective portals through the NE are formed at sites where the inner and outer nuclear membranes are fused, and the coincident assembly of ∼30 proteins into nuclear pore complexes occurs. These nuclear pore complexes are essential for the control of nucleocytoplasmic exchange. Many of the NE and nuclear pore proteins are thought to play crucial roles in gene regulation and thus are increasingly linked to human diseases.
Keywords: Developmental Biology; Cell Biology; General Biochemistry; Genetics and Molecular Biology; Molecular Biology

The role of nuclear pores in gene regulation, development and disease - Capelson, Maya; HETZER, Martin W (EMBO reports)
Nuclear-pore complexes (NPCs) are large protein channels that span the nuclear envelope (NE), which is a double membrane that encloses the nuclear genome of eukaryotes. Each of the typically 2,000–4,000 pores in the NE of vertebrate cells is composed of multiple copies of 30 different proteins known as nucleoporins. The evolutionarily conserved NPC proteins have the well-characterized function of mediating the transport of molecules between the nucleoplasm and the cytoplasm. Mutations in nucleoporins are often linked to specific developmental defects and disease, and the resulting phenotypes are usually interpreted as the consequences of perturbed nuclear transport activity. However, recent evidence suggests that NPCs have additional functions in chromatin organization and gene regulation, some of which might be independent of nuclear transport. Here, we review the transport-dependent and transport-independent roles of NPCs in the regulation of nuclear function and gene expression.
Keywords: Genetics; Molecular Biology; Biochemistry

Recruitment of functionally distinct membrane proteins to chromatin mediates nuclear envelope formation in vivo - Anderson, Daniel J.; Vargas, Jesse D.; Hsiao, Joshua P.; HETZER, Martin W (Journal of Cell Biology)
Formation of the nuclear envelope (NE) around segregated chromosomes occurs by the reshaping of the endoplasmic reticulum (ER), a reservoir for disassembled nuclear membrane components during mitosis. In this study, we show that inner nuclear membrane proteins such as lamin B receptor (LBR), MAN1, Lap2β, and the trans-membrane nucleoporins Ndc1 and POM121 drive the spreading of ER membranes into the emerging NE via their capacity to bind chromatin in a collaborative manner. Despite their redundant functions, decreasing the levels of any of these trans-membrane proteins by RNAi-mediated knockdown delayed NE formation, whereas increasing the levels of any of them had the opposite effect. Furthermore, acceleration of NE formation interferes with chromosome separation during mitosis, indicating that the time frame over which chromatin becomes membrane enclosed is physiologically relevant and regulated. These data suggest that functionally distinct classes of chromatin-interacting membrane proteins, which are present at nonsaturating levels, collaborate to rapidly reestablish the nuclear compartment at the end of mitosis.
Keywords: Cell Biology

ER membrane–bending proteins are necessary for de novo nuclear pore formation - Dawson, T. Renee; Lazarus, Michelle D.; HETZER, Martin W; Wente, Susan R. (Journal of Cell Biology)
Nucleocytoplasmic transport occurs exclusively through nuclear pore complexes (NPCs) embedded in pores formed by inner and outer nuclear membrane fusion. The mechanism for de novo pore and NPC biogenesis remains unclear. Reticulons (RTNs) and Yop1/DP1 are conserved membrane protein families required to form and maintain the tubular endoplasmic reticulum (ER) and the postmitotic nuclear envelope. In this study, we report that members of the RTN and Yop1/DP1 families are required for nuclear pore formation. Analysis of Saccharomyces cerevisiae prp20-G282S and nup133Δ NPC assembly mutants revealed perturbations in Rtn1–green fluorescent protein (GFP) and Yop1-GFP ER distribution and colocalization to NPC clusters. Combined deletion of RTN1 and YOP1 resulted in NPC clustering, nuclear import defects, and synthetic lethality with the additional absence of Pom34, Pom152, and Nup84 subcomplex members. We tested for a direct role in NPC biogenesis using Xenopus laevis in vitro assays and found that anti-Rtn4a antibodies specifically inhibited de novo nuclear pore formation. We hypothesize that these ER membrane–bending proteins mediate early NPC assembly steps.
Keywords: Cell Biology

Age-dependent deterioration of nuclear pore complexes causes a loss of nuclear integrity in postmitotic cells - D'Angelo, Maximiliano A.; Raices, Marcela; Panowski, Siler H.; HETZER, Martin W (Cell)
In dividing cells, nuclear pore complexes (NPCs) disassemble during mitosis and reassemble into the newly forming nuclei. However, the fate of nuclear pores in postmitotic cells is unknown. Here, we show that NPCs, unlike other nuclear structures, do not turn over in differentiated cells. While a subset of NPC components, like Nup153 and Nup50, are continuously exchanged, scaffold nucleoporins, like the Nup107/160 complex, are extremely long-lived and remain incorporated in the nuclear membrane during the entire cellular life span. Besides the lack of nucleoporin expression and NPC turnover, we discovered an age-related deterioration of NPCs, leading to an increase in nuclear permeability and the leaking of cytoplasmic proteins into the nucleus. Our finding that nuclear “leakiness” is dramatically accelerated during aging and that a subset of nucleoporins is oxidatively damaged in old cells suggests that the accumulation of damage at the NPC might be a crucial aging event.
Keywords: General Biochemistry; Genetics and Molecular Biology

Dark resonances for ground-state transfer of molecular quantum gases - Mark, Manfred; Danzl, Johann G; Haller, Elmar; Gustavsson, Mattias; Bouloufa, Nadia; Dulieu, Olivier; Salami, Houssam; Bergeman, Thomas; Ritsch, Helmut; Hart, Russell; Nägerl, Hanns (Applied Physics B: Lasers and Optics)
One possible way to produce ultra-cold, high-phase-space-density quantum gases of molecules in the rovibronic ground state is given by molecule association from quantum-degenerate atomic gases on a Feshbach resonance and subsequent coherent optical multi-photon transfer into the rovibronic ground state. In ultra-cold samples of Cs2 molecules, we observe two-photon dark resonances that connect the intermediate rovibrational level |v=73,J=2 with the rovibrational ground state |v=0,J=0 of the singlet X 1 ∑ g + ground-state potential. For precise dark resonance spectroscopy we exploit the fact that it is possible to efficiently populate the level |v=73,J=2 by two-photon transfer from the dissociation threshold with the stimulated Raman adiabatic passage (STIRAP) technique. We find that at least one of the two-photon resonances is sufficiently strong to allow future implementation of coherent STIRAP transfer of a molecular quantum gas to the rovibrational ground state |v=0,J=0.

Realization of an excited, strongly correlated quantum gas Phase - Haller, Elmar; Gustavsson, Mattias; Mark, Manfred; Danzl, Johann G; Hart, Russell; Pupillo, Guido; Nägerl, Hanns (Science)
Ultracold atomic physics offers myriad possibilities to study strongly correlated many-body systems in lower dimensions. Typically, only ground-state phases are accessible. Using a tunable quantum gas of bosonic cesium atoms, we realized and controlled in one-dimensional geometry a highly excited quantum phase that is stabilized in the presence of attractive interactions by maintaining and strengthening quantum correlations across a confinement-induced resonance. We diagnosed the crossover from repulsive to attractive interactions in terms of the stiffness and energy of the system. Our results open up the experimental study of metastable, excited, many-body phases with strong correlations and their dynamical properties.

Deeply bound ultracold molecules in an optical lattice - Danzl, Johann G; Mark, Manfred; Haller, Elmar; Gustavsson, Mattias; Hart, Russell; Liem, Andreas; Zellmer, Holger; Nägerl, Hanns (New Journal of Physics)
We demonstrate efficient transfer of ultracold molecules into a deeply bound rovibrational level of the singlet ground state potential in the presence of an optical lattice. The overall molecule creation efficiency is 25%, and the transfer efficiency to the rovibrational level |v = 73, J = 2) is above 80%. We find that the molecules in |v = 73, J = 2) are trapped in the optical lattice, and that the lifetime in the lattice is limited by optical excitation by the lattice light. The molecule trapping time for a lattice depth of 15 atomic recoil energies is about 20 ms. We determine the trapping frequency by the lattice phase and amplitude modulation technique. It will now be possible to transfer the molecules to the rovibrational ground state |v = 0, J = 0) in the presence of the optical lattice.

Precision molecular spectroscopy for ground state transfer of molecular quantum gases - Danzl, Johann G; Mark, Manfred; Haller, Elmar; Gustavsson, Mattias; Bouloufa, Nadia; Dulieu, Olivier; Ritsch, Helmut; Hart, Russell; Nägerl, Hanns (Faraday Discussions)
One possibility for the creation of ultracold, high phase space density quantum gases of molecules in the rovibronic ground state relies on first associating weakly-bound molecules from quantum-degenerate atomic gases on a Feshbach resonance and then transferring the molecules via several steps of coherent two-photon stimulated Raman adiabatic passage (STIRAP) into the rovibronic ground state. Here, in ultracold samples of Cs2 Feshbach molecules produced out of ultracold samples of Cs atoms, we observe several optical transitions to deeply-bound rovibrational levels of the excited 0 u+ molecular potentials with high resolution. At least one of these transitions, although rather weak, allows efficient STIRAP transfer into the deeply-bound vibrational level v = 73> of the singlet X 1Σg+ ground state potential, as recently demonstrated (J. G. Danzl, E. Haller, M. Gustavsson, M. J. Mark, R. Hart, N. Bouloufa, O. Dulieu, H. Ritsch, and H.-C. Nägerl, Science, 2008, 321, 1062). From this level, the rovibrational ground state v = 0, J = 0> can be reached with one more transfer step. In total, our results show that coherent ground state transfer for Cs2 is possible using a maximum of two successive two-photon STIRAP processes or one single four-photon STIRAP process.

Capture and modeling of non-linear heterogeneous soft tissue - Bernd Bickel; Bac̈her, Moritz; Otaduy, Miguel A; Matusik, Wojciech; Pfister, Hanspeter; Groß, Markus S
This paper introduces a data-driven representation and modeling technique for simulating non-linear heterogeneous soft tissue. It simplifies the construction of convincing deformable models by avoiding complex selection and tuning of physical material parameters, yet retaining the richness of non-linear heterogeneous behavior. We acquire a set of example deformations of a real object, and represent each of them as a spatially varying stress-strain relationship in a finite-element model. We then model the material by non-linear interpolation of these stress-strain relationships in strain-space. Our method relies on a simple-to-build capture system and an efficient run-time simulation algorithm based on incremental loading, making it suitable for interactive computer graphics applications. We present the results of our approach for several non-linear materials and biological soft tissue, with accurate agreement of our model to the measured data.